Interleukin 10, monocytes and increased risk of early infection in ischaemic stroke. Issue 11 (16th October 2006) - Chamorro, Á; Amaro, S; Vargas, M; Obach, V; Cervera, Á; Torres, F; Planas, A M
Abstract : Background and purpose: : The pathophysiology of stroke-associated infection (SAI) is uncertain. The cytokine profile and peripheral white cell response were assessed in patients with or without SAI. Methods: The incidence of SAI was assessed in 110 patients with ischaemic stroke allocated antibiotic prophylaxis or placebo within 24 h of clinical onset. Peripheral white cell counts, interleukin (IL)6, tumour necrosis factor (TNF)α and IL10 were measured in plasma. Results: 17 (15%) patients developed infection and showed time-dependent increases of total white cell count, neutrophils, monocytes, lymphocytes, IL6 and IL10, whereas TNFα and the TNFα/IL10 ratio decreased. In logistic regression, IL10 (odds ratio (OR) 1.08, 95% confidence interval (CI) 1.01 to 1.16), monocyte count (OR 1.42, 95% CI 1.08 to 1.87) and National Institute for Health Stroke Survey score on admission (OR 1.17, 95% CI 1.05 to 1.31) were independent predictors of systemic infection. Conclusions: SAI is associated with stroke severity, excessive IL10-mediated response and an increased number of circulating monocytes. These results support the finding that acute ischaemic brain injury triggers a blood-borne anti-inflammatory response that decreases the antimicrobial drive of the immune system.